Automatic control and user interface for central tire inflation system - Björgvin Rúnar Þórhallsson 1989- (2015)
The aim of this study was to compile a list of requirements for the automatic control system and user interface part of central tire inflation system (CTIS) specialized for off road snow driving conditions in Iceland. Furthermore to design and build a prototype that fulfils all requirements. CTIS enables the driver of a vehicle to adjust the tire pressure while the vehicle is moving. It can reduce the risk of damaging tires because of over deflated tires, increase average travelling speed and reduce fuel consumption. Manual CTI systems have been used in Iceland for snow driving purposes in modified 4x4 vehicles and are getting more popular. Commercial automatic solutions exists but none fulfils the requirements of Icelandic drivers of snow driving vehicles. Solutions that are aimed to fulfil this market gap are currently being developed in Iceland. Experienced people within the field of modified 4x4 vehicles in Iceland were interviewed to collect opinions about requirements for the system. Experiments were conducted on realistic setups of pneumatic systems to analyse and model the system as steps toward fulfilling requirements. The designed and build prototype fulfils 12 out of 18 requirements defined for the system, more experiments are needed to confirm four and implementation towards two requirements were not finished. The list of requirements coming out of this study is the first one compiled for Icelandic snow driving conditions. It is believed that it will be a cornerstone in the discussion and development for automatic control systems in Iceland in the coming years. Markmið þessa verkefnis var annars vegar að komast að þeim kröfum sem notandaviðmót og sjálfstýring fyrir úthleypibúnaði í íslenska fjallajeppa þarf að uppfylla. Jafnframt var markmiðið að hanna og smíða sjálfstýringu og notandaviðmót sem uppfyllir allar kröfur. Úrhleypibúnaður gerir ökumanni kleift að stilla loftþrýsting í dekkjum á meðan á akstri setendur. Slíkur búnaður getur dregið úr hættu á dekkjaskemmdum af völdum aksturs á of ...